New onset headache during delivery and postpartum: Clinical characteristics of a case series - Allais, Gianni; Chiarle, Giulia; Sinigaglia, Silvia; Mollo, Elena M.; Perin, Giada; Pizzino, Francesca; Benedetto, Chiara (Frontiers in Neurology, 2022)
Introduction There are abundant studies on headache and migraine in women but few or none about their occurrence during labor, delivery, and postpartum (2 hours after delivery) owing to the low incidence. A headache attack can be debilitating when a woman is trying to manage labor pain. Research at our Women's Headache Center within the Department of Gynecology and Obstetrics has begun to shed light on this potential association. Methods For the present study 474 women with singleton pregnancy were enrolled. A headache questionnaire was administered at two time points. Headache history was investigated on admission to prenatal care at 36 weeks gestation. The women were followed by a midwife who monitored labor progression and recorded the onset and features of headache pain. During examination before hospital discharge at 3 days post-delivery, the headache questionnaire was reviewed by a headache specialist who differentiated headache type according to International Classification of Headache Disorders (3rd edition) criteria. Results Data analysis showed that 145/474 women had a history of headache: 65/145 (44.82%) reported a diagnosis of migraine. Eight reported experiencing a probable migraine attack (4 with aura) and one reported probable tension-type headache during labor or postpartum. All nine women who reported migraine/headache attack during labor had no previous history of headache or neurological illness. All had vaginal delivery. No onset of headache pain in patients with a previous history of headache was noted during delivery and postpartum. Discussion The onset of a headache attack during labor in women who usually do not experience headache suggests other pathogenic mechanisms underlying the attack and merits further study.